2019
DOI: 10.9734/jeai/2019/v37i530277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization on the Growth and Quality of Tamarind Seedlings Irrigated with Saline Water

Abstract: Aims: The objective of this work was to evaluate the effect of nitrogen fertilization on the production of Tamarindus indica L. seedlings irrigated with saline water. Study Design:  A randomized complete block design was used in a 4 x 4 factorial scheme, whose factors were the electrical conductivity levels of the irrigation water. Place and Duration of Study: The work was conducted under protected environment conditions (greenhouse) at the Federal University of Campina Grande, Center for Agro-Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…All these factors have damaging effects on physiological and biochemical processes of plants and consequently, salt stressed plants show poor performance (Hasanuzzaman et al, 2013). Similarly, Fatima et al (2019) concluded that salinity levels of 3.7 and 5.2 dS m-1 had detrimental effect on shoot height and stem diameter of tamarind plants which support the current findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…All these factors have damaging effects on physiological and biochemical processes of plants and consequently, salt stressed plants show poor performance (Hasanuzzaman et al, 2013). Similarly, Fatima et al (2019) concluded that salinity levels of 3.7 and 5.2 dS m-1 had detrimental effect on shoot height and stem diameter of tamarind plants which support the current findings.…”
Section: Discussionsupporting
confidence: 86%
“…Increasing levels of saline water compromised growth parameters of tamarind seedling and higher intensity of saline water significantly reduced seedling biomass, leaf area, chlorophyll contents and carotenoids. Fatima et al (2019) concluded that saline water irrigation with 2.15 dS m-1 caused an acceptable reduction of 10% in growth variables of tamarind plant while further increase in salinity i.e., 3.7 and 5.2 dS m-1 had detrimental effect on shoot height and stem diameter. Previously El-Siddig et al (2004) exposed the tamarind seedlings to 0, 30, 60 and 120 mM NaCl solution.…”
Section: Introductionmentioning
confidence: 96%